3D Printing in Spine Surgery: Current and Emerging Applications (Transactions on Additive Manufacturing Meets Medicine, 2021)
The versatility of 3D printing allows its benefits and applications to address many areas and unmet clinical needs within spine surgery. The replicative ability of 3D printing can be extended to safely simulate surgical and anatomic conditions by mimicking the structural and textural anatomy, improving the quality of surgical training/teaching and decreasing the dependence on cadavers. At present, surgical instrumentation is trending towards patient specific and pathology specific implants. Patient specific implants cater towards the geometrical aspect of patients’ anatomy, while pathology specific implants cater towards the biomechanical and biological aspects of the patients’ anatomy that has been influenced by their pathology i.e., cancer or degenerative conditions. 3D printing’s versatility in geometrical replication and compatibility with a wide array of materials is highly applicable to these schools of thought. Furthermore, these same qualities can be extended towards more emerging techniques such as targeted or localized therapies.Naresh Kumar has been practicing medicine for 35 years and spine surgery for 25 years. He is a key opinion leader in the field of metastatic spine disease and is involved in implant development for spinal devices, particularly in the field of metastatic spine tumour surgery. A/Prof Naresh Kumar was the previous president for the Singapore Orthopaedic Association (SOA) in 2019 and is the current president for the Pacific and Asian Society of Minimally Invasive Spine Surgery (PASMISS). He is also the lead advisor for development of Icotec ag’s posterior cervical fixation system. He also has been awarded two grants by the National Additive Manufacturing Innovation Cluster (NAMIC) to develop implant materials for manufacturing pathology specific spinal implants. Naresh Kumar has over a hundred peer-reviewed publications which comprise major health practice changing techniques and innovations in metastatic spine tumour surgery and implant failure. Some examples include the application of intraoperative cell salvage (IOCS) in MSTS, the novel concepts of asymptomatic implant failure after MSTS, re-admission free survival (ReAFS), and the spinal metastatic invasiveness index (SMII).
Keywords: Spine surgery